Endurance training at altitude - Saunders, P. U.; Pyne, D. B.; Gore, C. J. (High Altitude Medicine & Biology, 2009)
Since the 1968 Olympic Games when the effects of altitude on endurance performance became evident, moderate altitude training (2000 to 3000m) has become popular to improve competition performance both at altitude and sea level. When endurance athletes are exposed acutely to moderate altitude, a number of physiological responses occur that can comprise performance at altitude; these include increased ventilation, increased heart rate, decreased stroke volume, reduced plasma volume, and lower maximal aerobic power (o2max) by 15% to 20%. Over a period of several weeks, one primary acclimatization response is an increase in the volume of red blood cells and consequently of o2max. Altitudes >2000m for >3 weeks and adequate iron stores are required to elicit these responses. However, the primacy of more red blood cells for superior sea-level performance is not clear-cut since the best endurance athletes in the world, from Ethiopia (2000 to 3000m), have only marginally elevated hemoglobin concentrations. The substantial reduction in o2max of athletes at moderate altitude implies that their training should include adequate short-duration (1 to 2min), high-intensity efforts with long recoveries to avoid a reduction in race-specific fitness. At the elite level, athlete performance is not dependent solely on o2max, and the "smallest worthwhile change" in performance for improving race results is as little as 0.5%. Consequently, contemporary statistical approaches that utilize the concept of the smallest worthwhile change are likely to be more appropriate than conventional statistical methods when attempting to understand the potential benefits and mechanisms of altitude training.